Comparison of Outcomes Between Anti-Nuss Operation and Modified Anti-Nuss Operation Using a Flexible Plate for Correcting Pectus Carinatum: A Retrospective Study - Wang, Lei; Liu, Juan; Shen, Saie; Li, Yao; Feng, Tienan; Li, Guoqing; Xiao, Haibo; Hu, Fengqing (Frontiers in Surgery, 2021)
Introduction: Shortcoming of anti-Nuss operation is gradually found in the clinical practice. A new steel plate designed by our department was introduced. However, there is limited evidence regarding its safety and efficacy. A single center, retrospective study was conducted to explore the efficacy and safety of anti-nuss operation vs modified anti-nuss operation using a flexible plate and therefore increase the existing evidence on modified anti-nuss operation. Methods: From January 2014 to August 2019, patients with pectus carinatum in all underwent surgery were included naturally. 53 patients received modified procedure with a new steel plate as treatment group while 43 received anti-Nuss procedure as control group. Outcomes analysis was performed using SPSS to compare the intraoperative and postoperative short-term outcomes. Results: The operation time was 75.23±11.90 minutes, the postoperative hospital stay was 3.42±0.95 days, and the operation time for plate removal was 40.60±3.47 minutes in the treatment group, which included 4 cases of complications. The operation time was 82.45±9.30 minutes, the postoperative hospital stay was 4.64±1.53 days, and the operation time for plate removal was 60.30±9.75 minutes in the control group, which included 5 cases of complications. There was no significant difference in the length of incision, postoperative Haller index, cost, postoperative surgical outcome and incidence of complications between the two groups. There were significant differences in the operation time, postoperative hospital stay and operation time for plate removal. Conclusion: Our data reveal the main clinical outcome between anti-Nuss operation and modified anti-nuss operation were similar. However, modified procedure for pectus carinatum has shorter operation time, postoperative hospital stay, and operation time for plate removal.